2019
DOI: 10.1111/iwj.13230
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of home‐based exercise programme on physical function after hip fracture: a systematic review and meta‐analysis of randomised controlled trials

Abstract: We performed a meta-analysis to evaluate the effect of home exercise programmes on body function after hip fractures. A computerised literature search was performed for published trials in PubMed, EMBASE, CENTRAL, and Cochrane Database of Systematic Reviews. Randomised trials were selected investigating home-based exercise programmes vs usual care without home-based exercise in hip fracture patients. Physical health (measured by Short Form 36), normal gait speed, fast gait speed, balance, instrumental activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 27 publications
5
26
3
Order By: Relevance
“…Over recent decades other models of home-based rehabilitation (HBR) have been developed in addition to the classical model. Two systematic reviews were published recently ( 8 , 9 ) that evaluated the effectiveness of HBR for patients with fractures of the femoral neck, but most studies included in the review related to ongoing rehabilitation processes and not intensive rehabilitation immediately after surgery. Table 1 shows a summary of the main findings of six studies ( 10 15 ) that compared the effectiveness of HBR with that of standard inpatient rehabilitation (IR).…”
Section: Introductionmentioning
confidence: 99%
“…Over recent decades other models of home-based rehabilitation (HBR) have been developed in addition to the classical model. Two systematic reviews were published recently ( 8 , 9 ) that evaluated the effectiveness of HBR for patients with fractures of the femoral neck, but most studies included in the review related to ongoing rehabilitation processes and not intensive rehabilitation immediately after surgery. Table 1 shows a summary of the main findings of six studies ( 10 15 ) that compared the effectiveness of HBR with that of standard inpatient rehabilitation (IR).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, additional studies need to be conducted to determine the clinical significance of balance training. Chen et al [ 25 ] found that a home-based exercise program had a positive, although not significant, effect on physical function after hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, many scholars have conducted extensive research in the area of post-operative rehabilitation of hip fracture patients [4]. Different exercises and activity movements to be performed during rehabilitation have been proposed [16,17].…”
Section: Related Workmentioning
confidence: 99%
“…It plays a pivotal role in restoring physical functionality, healing the injured hip, and supporting muscle strength. Evidence shows that intensive rehabilitation plays a role in functional performance, quality of life, and achieving optimal rehabilitation outcomes [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation